Aktifitas Antibiotik Ceftazidime-Avibactam Dan Ceftaroline Secara In Vitro Terhadap Isolat Klinis Di Pekanbaru - Chandra Wijaya (Fakultas Kedokteran Universitas Riau, 2023)
Ceftaroline and Ceftazidime–avibactam are relatively new antibiotics that show good effectiveness against antibiotic-resistant pathogens. Both of these antibiotics are now available worldwide, but reports of resistance to them are also starting to emerge. This study aimed to evaluate the in vitro activity of the antibiotic Ceftazidime-avibactam combination of 100 clinical isolates consisting of Enterobacteriaceae and Pseudomonas aeruginosa bacteria and to evaluate the antibiotic effect of Ceftaroline against 100 clinical isolates of Enterobacteriaceae and Staphylococcus sp. This study is observational with cross-sectional study design. The study was conducted at the microbiology laboratory of a private hospital at Pekanbaru Riau in Januari-June 2021. There were 100 clinical isolates tested with Ceftaroline and Ceftazidime-avibactam. The sensitivity to Ceftaroline and Ceftazidime-avibactam were reported as a number isolate and percentage. The results showed the sensitivity of bacteria K. pneumoniae, E. coli, Enterobacter sp, and P. aeruginosa, to Ceftazidime-Avibactam were 87%, 90%, 66%, and 82%, respectively. The sensitivity of the antibiotic Ceftaroline to the bacteria K. pneumoniae, E. coli, Enterobacter sp and Staphylococcus sp. were 39%, 54%, 36.4%, 67% and 75%, respectively. Based on these results, the antibiotic ceftazidime avibactam can be used for the treatment of suitable pathogenic infections because of its fairly good sensitivity (>80%) to Enterobacteriaceae and P. aeruginosa bacteria. Ceftaroline antibiotics are not recommended to be used as a therapeutic option, because of the high resistance to Enterobacteriaceae and Staphylococcus sp. Further research is needed to determine the molecular mechanism of resistance to Ceftaroline antibiotics